RESPONSIBILITIES OF STATES SPONSORING PERSONS AND ENTITIES WHO CONDUCT ACTIVITIES IN THE INTERNATIONAL SEABED AREA - Kinanti, Fatma Muthia (UI Scholars Hub, 2021)
The exploitation of seabed has been regulated in the international sea law regime, namely in UNCLOS 1982 and in its modification regulations, the 1994 Implementing Agreement. This regime regulates the sponsorship mechanism whereby companies wishing to carry out activities in the international seabed must cooperate with states participating in UNCLOS 1982. In addition to providing obligations to companies, the international sea law regime also imposes obligations on the sponsoring state. This obligation is related to the steps that the participating states must take to ensure that no violations or damage occur during the project. This article will discuss the legal relationship between the contractor and the sponsoring state, specifically the extent to which the sponsoring state is responsible for the activities of the sponsoring contractor in the ISBA region. To answer this question, the following will be examined: the provisions of the international maritime legal framework, UNCLOS 1982 and related international regulations and examine jurisprudence in related cases, especially in the Advisory Opinion provided by ITLOS in the cases of Responsibilities and Obligations of States sponsoring persons and entities with respect to activities in ISBA (2010). It was found that the international legal framework regulates the state’s responsibility to ensure that no violations or damage occur during these activities. The Advisory Opinion then provided specific restrictions on the extent to which the “responsibility to ensure” must be carried out by the state and whether the state may be liable to pay losses due to damage caused by the activities.